Methionine Antagonizes para-Aminosalicylic Acid Activity via Affecting Folate Precursor Biosynthesis in Mycobacterium tuberculosis - Howe, Michael D.; Kordus, Shannon L.; Cole, Malcolm S.; Bauman, Allison A.; Aldrich, Courtney C.; Baughn, Anthony D.; Minato, Yusuke (Frontiers in Cellular and Infection Microbiology, 2018)
para-Aminosalicylic acid (PAS) is a second-line anti-tubercular drug that is used for the treatment of drug-resistant tuberculosis (TB). PAS efficacy in the treatment of TB is limited by its lower potency against Mycobacterium tuberculosis relative to many other drugs in the TB treatment arsenal. It is known that intrinsic metabolites, such as para-aminobenzoic acid (PABA) and methionine, antagonize PAS and structurally related anti-folate drugs. While the basis for PABA-mediated antagonism of anti-folates is understood, the mechanism for methionine-based antagonism remains undefined. In the present study, we used both targeted and untargeted approaches to identify factors associated with methionine-mediated antagonism of PAS activity. We found that synthesis of folate precursors as well as a putative putative amino acidamino acid transporter, playdesignated MetM play crucial roles in this process. Disruption of metM by transposon insertion resulted in a ≥100-fold decrease in uptake of methionine in M. bovis BCG, indicating that metM is the major facilitator of methionine transport in M. bovis BCG. We also discovered that intracellular biotin confers intrinsic PAS resistance in a methionine-independent manner. Collectively, our results demonstrate that methionine-mediated antagonism of anti-folate drugs occurs through sustained production of folate precursors.